The role of obesity, type 2 diabetes, and metabolic factors in gout: A Mendelian randomization study - Yang, Yang; Xian, Wei; Wu, Dide; Huo, Zijun; Hong, Shubin; Li, Yanbing; Xiao, Haipeng (Frontiers in Endocrinology, 2022)
Abstract Background: Several epidemiological studies have reported a possible correlation between risk of gout and metabolic disorders including type 2 diabetes, insulin resistance, obesity, dyslipidemia and hypertension. However, it is unclear if this association is causal. Methods: We used Mendelian randomization (MR) to evaluate the causal relation between metabolic conditions and gout or serum urate concentration by inverse-variance weighted (conventional) and weighted median methods. Furthermore, MR-Egger regression and MR-pleiotropy residual sum and outlier (PRESSO) method were used to explore pleiotropy. Genetic instruments for metabolic disorders and outcome (gout and serum urate) were obtained from several genome-wide association study which mainly European ancestry. Results: Conventional MR analysis showed a robust causal association of increasing obesity measured by body mass index (BMI), high-density lipoprotein cholesterol (HDL) and systolic blood pressure (SBP) with risk of gout. A causal relationship between fasting insulin, BMI, HDL, triglycerides (TG), SBP, alanine aminotransferase (ALT) and serum urate was also observed. These results were consistent in weighted median method and MR-PRESSO after removing outliers identified. Our analysis also indicated that HDL and serum urate as well as gout have a bidirectional causal effect on each other. Conclusions: Our study suggested causal effects between glycemic traits, obesity, dyslipidemia, blood pressure, liver function and serum urate as well as gout, which implies that metabolic factors contribute to the development of gout via serum urate. The potential benefit of sound management of increased serum urate in patients with obesity, dyslipidemia, hypertension and liver dysfunction.